2011
DOI: 10.1155/2011/309068
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Hypertension after Parathyroidectomy of Patients Suffering from Primary Hyperparathyroidism

Abstract: Background. Primary hyperparathyroidism (PHPT) is one of the most common endocrine conditions and is accompanied by hypertension and increased cardiovascular mortality. The purpose of this study was to evaluate the effect of parathyroidectomy on systolic and diastolic blood pressure (BP) in hypertensive patients with PHPT and whether hypertension occurs more frequently in PHPT than in control group. Methods. A total of 1020 patients with proved PHPT who underwent surgery were compared with with 1020 age, sex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 27 publications
2
35
0
4
Order By: Relevance
“…Hypertension secondary to pHPT is still being debated [22] . The 54.1% incidence rate of hypertension in pHPT is within the range of 20-69% reported in various studies [5,23,24] . This large variation in reported incidence could be due to variations between different authors due to differences in blood pressure measurement criteria of hypertension and different patient characteristics.…”
Section: Discussionsupporting
confidence: 76%
“…Hypertension secondary to pHPT is still being debated [22] . The 54.1% incidence rate of hypertension in pHPT is within the range of 20-69% reported in various studies [5,23,24] . This large variation in reported incidence could be due to variations between different authors due to differences in blood pressure measurement criteria of hypertension and different patient characteristics.…”
Section: Discussionsupporting
confidence: 76%
“…It was slightly higher in females. This study has been drawn from our group of PHPT patients (Broulík et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…27 The surgical patients in our sample showed no improvement in cardiovascular risk factors at one year of follow-up. As regards HBP, some studies, 12,28 but not all, 29 have shown blood pressure decreases after surgery. It should be noted that in studies showing no changes, mean baseline blood pressure values were not excessively elevated, as occurred in our study.…”
Section: Discussionmentioning
confidence: 99%
“…3,12,13 It has also been shown that PHP induces left ventricular hypertrophy in the absence of HPB, and that PTH levels correlate to left ventricular mass. 14 After surgery, regression of left ventricular hypertrophy has been reported in a variable time period ranging from one to five years, 15 but subsequent studies do not support this effect in patients with mild PHP.…”
Section: Discussionmentioning
confidence: 99%